Critical Discourse Analysis in the Education Community to Respond the Hoax Based on Technology and Information - Mas’ud Muhammadiah; Arwin Tannuary; Rona Romadhianti; Endang Fatmawati; Herman Herman (STAI Hubbulwathan Duri, 2023)
The research looked at how people in the Education community responded to the hoax phenomenon from the point of view of technology and information. This research aims to improve the educational component's ability to analyse different kinds of information or news. This will make it less likely that fake information will be used as a talking point or a guide. The method used is qualitative with critical discourse analysis, where the program's implementation is through the ASSURE method. The number of respondents is 60 consisting of teachers, parents and students in the sixth grade of an elementary school in Medan city. The technique used by researchers to gather data involves grouping various data, processing it in accordance with the aim to be recorded, and then deconstructing it using an essential conversation investigation preparation software created using the ASSURE approach. The technique of analyzing data was by implementing the six stages in the ASSURE model, which represent three other stages: pre-program, program implementation and post-program. The results show that critical discourse analysis through the basic conversation investigation program using the ASSURE method has proven to be effective and can be used to prevent the spread of hoax information that can cause various disputes.